2019
DOI: 10.1002/col.22443
|View full text |Cite
|
Sign up to set email alerts
|

Color‐emotion associations in interiors

Abstract: Emotional reactions to red, green, blue, and gray colors in a living room were investigated using a self‐report measure. Participants first watched a short video of a 3D model of a living room. Next, they were asked to match the living rooms with facial expressions of six basic emotions. The most stated emotions associated for the red room were disgust and happiness, while the least stated emotions were sadness, fear, anger, and surprise; for the green room, neutral and happiness were the most stated emotions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 17 publications
2
41
1
1
Order By: Relevance
“…Nonetheless, orange with different value and chroma levels is selected for positive meanings as well, which supports the fact that colour meaning can vary in RITs depending on all colour attributes. Previous studies suggested that green colour in interiors has ‘home’ and ‘calming’ meanings 16 and ‘happiness’ in living room 14 . Similarly, in this study, green colours are selected for ‘beautiful’ and ‘pleasant’ for many RITs.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Nonetheless, orange with different value and chroma levels is selected for positive meanings as well, which supports the fact that colour meaning can vary in RITs depending on all colour attributes. Previous studies suggested that green colour in interiors has ‘home’ and ‘calming’ meanings 16 and ‘happiness’ in living room 14 . Similarly, in this study, green colours are selected for ‘beautiful’ and ‘pleasant’ for many RITs.…”
Section: Resultsmentioning
confidence: 91%
“…Participants did not receive any payment or encouragement. That provided a group of 20 individuals (16 females and 4 males) considering the previous study 14 revealed no gender difference in colour emotions for living rooms. As they needed to recall memories and engage with their knowledge, they needed to spend a very long time on each response to colour associations.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Different colors give people different perceptions that trigger psychological responses that may also result in physiological reactions. For example, the red band of color is lively and warm while the green represents life and is calming [28]. Kaufman and Lohr found that all trees with green and red color appearances evoked positive responses [23], but the preference also depends on the environment [29] and other indicators.…”
mentioning
confidence: 99%
“…Color is an important design element and has a strong relationship with emotions [31]. Green, reminiscent of plants, and blue, reminiscent of the sky and water, are quiet and positive, and they encourage stability [32].…”
Section: Comfortmentioning
confidence: 99%